Effect of prior general anesthesia or sedation and antiseizure drugs on the diagnostic utility of wireless video electroencephalography in dogs. (13th July 2020) - Parmentier, Thomas; Monteith, Gabrielle; Cortez, Miguel A.; Wielaender, Franziska; Fischer, Andrea; Jokinen, Tarja S.; Lohi, Hannes; Sanders, Sean; Sammut, Veronique; Tai, Tricia; James, Fiona M. K.
Abstract: Background: Ambulatory wireless video electroencephalography (AEEG) is the method of choice to discriminate epileptic seizures from other nonepileptic episodes. However, the influence of prior general anesthesia (GA), sedation, or antiseizure drug (ASD) on the diagnostic ability of AEEG is unknown. Hypothesis/Objectives: The use of sedation/GA or ASD treatment before AEEG recording may affect the diagnostic ability of AEEG and the time to first abnormality on AEEG. Animals: A total of 108 client‐owned dogs undergoing ambulatory AEEG for paroxysmal episodes. Methods: Retrospective cohort study. Proportions of diagnostic AEEG and time to first abnormality were compared between dogs that received sedation/GA or neither for instrumentation as well as dogs receiving at least 1 ASD and untreated dogs. Results: Ambulatory EEG was diagnostic in 60.2% of all dogs including 49% of the sedation/GA dogs and 68% of dogs that received neither (odds ratio [OR], 2.25; 95% confidence interval [CI], 1.02‐5.00; P = .05). The AEEG was diagnostic in 51% of dogs receiving at least 1 ASD and 66% of untreated dogs (OR, 1.95; 95% CI, 0.9‐4.3; P = .11). No difference was found in time to first abnormality between sedation/GA or neither or ASD‐treated or untreated dogs ( P = .1 and P = .3 respectively). Ninety‐five percent of dogs had at least 1 abnormality within 277 minutes. Conclusion and Clinical Importance: Sedation/GA and concurrent ASD administration were not identified as confounding factors for decreasing AEEG diagnostic capability nor did they delay the time to first abnormality. A 4‐hour minimal recording period is recommended.